2015
DOI: 10.1364/oe.23.000929
|View full text |Cite
|
Sign up to set email alerts
|

Bio-inspired variable imaging system simplified to the essentials: modelling accommodation and gaze movement

Abstract: A combination of an aspherical hybrid diffractive-refractive lens with a flexible fluidic membrane lens allows the implementation of a light sensitive and wide-aperture optical system with variable focus. This approach is comparable to the vertebrate eye in air, in which the cornea offers a strong optical power and the flexible crystalline lens is used for accommodation. Also following the natural model of the human eye, the decay of image quality with increasing field position is compensated, in the optical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 12 publications
1
9
0
1
Order By: Relevance
“…Other corneal shapes have also been reported by several authors [ 16 , 27 , 31 , 54 , 56 ], who have used double-convex (biconvex) lenses. Single surface lenses have also been used, with convex-plano lenses being very common [ 15 , 29 , 33 , 34 , 35 , 40 , 63 , 64 , 72 , 85 ], due to the fact that the human posterior cornea has a relatively small contribution to the overall performance, essentially due to the small difference in refractive index between the aqueous fluid and the cornea, and the difficulty in replicating the posterior cornea [ 64 ].…”
Section: Components Of a Physical Eye Modelsupporting
confidence: 64%
See 1 more Smart Citation
“…Other corneal shapes have also been reported by several authors [ 16 , 27 , 31 , 54 , 56 ], who have used double-convex (biconvex) lenses. Single surface lenses have also been used, with convex-plano lenses being very common [ 15 , 29 , 33 , 34 , 35 , 40 , 63 , 64 , 72 , 85 ], due to the fact that the human posterior cornea has a relatively small contribution to the overall performance, essentially due to the small difference in refractive index between the aqueous fluid and the cornea, and the difficulty in replicating the posterior cornea [ 64 ].…”
Section: Components Of a Physical Eye Modelsupporting
confidence: 64%
“…Förster et al [ 54 ] created an artificial eye to model accommodation and gaze movement. It used an aspherical surface and diffractive optical element to model the cornea and a tunable fluidic membrane crystalline lens, comprising an optical group and a CCD camera.…”
Section: Eye Models For Human Visionmentioning
confidence: 99%
“…According to the test results, it is shown that the proposed approach for focusing on objects located on different distances is similar to accommodation characteristics of the human eye, where the cornea possesses maximum optical power, but the shape-variable lens has low optical power. A similar architecture of an eye-like optical system based on the same operating principle was reported in [68]. However, the authors provided the system with an ability to mimic saccadic eye movement by means of mechanically tilting the system at small angles.…”
Section: The Hybrid Optical Elements Mimic the Eye's Optical Systemmentioning
confidence: 96%
“…The refractive index and the Abbe number are the key parameters for optical polymers used in geometrical optics. The refractive index for a typical optical polymer was as low as 1.49-1.5 [11][12]. The contact lens made of these low refractive index polymers has the disadvantage of being too thick at both the center and edge.…”
Section: Introductionmentioning
confidence: 99%